Analysis of the Influence of Social Capital, Innovation, and Market Orientation on the Growth of Micro and Small Enterprises in the Special Region of Jakarta - Sudirjo, Frans; Hendratri, Bhaswarendra Guntur; Desiyanti, Rika; Sudarmanto, Eko (Westscience Press, 2024)
This study examines the effects of social capital, innovation, and market orientation on the growth of Micro and Small Enterprises (MSEs) in the Special Capital Region of Jakarta. Using a quantitative research approach, data were collected from 160 MSEs through a structured questionnaire, and the relationships between the variables were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that all three factors—social capital, innovation, and market orientation—significantly contribute to the growth of MSEs. Innovation was identified as the most critical factor, followed by social capital and market orientation. The findings highlight the importance of fostering innovation, adopting market-oriented strategies, and leveraging social networks for the sustainable growth of MSEs. This study provides valuable insights for entrepreneurs and policymakers on how to support the development of MSEs in competitive urban environments.